Retorica e costruzione del consenso in Tucidide: il caso di Mitilene / Rhetoric and building consensus in Thucydides: the case of Mytilen - Cusumano, Nicola (Rivista Italiana di Filosofia del Linguaggio)
In his account of the Peloponnesian war, Thucydides explicitly insists on some dilemmas linked to the wider matter of deliberative process: in particular, the relationship between nature, profit and justice, truth and lie, speech and action. The story of the uprising of Mytilene is particularly useful, intertwining the antilogy between the two speakers (Cleon and Diodotus) with the so-called metanoia: the Athenian deliberative rethinking puts on focus the complex problems of the building of consensus in the democratic decision-making processes. Here we examine only one point of the two rich and articulate speeches: the opportunity of discussing again what has been already decided in a correct way from a procedural point of view. The assembly’s debate allows to put on focus the profile of a perfect “decision-maker”, which is sketched by both speakers in a different manner. To the harassment of Cleon on the necessity of keeping unchangeable undertaken decisions, Diodotus opposes the necessity of a change of decision and thus of a deliberative reconsideration, for the sake of "eubolia" if it interests Athens. Thank to this Thucydides has the opportunity to highlight the difficult, but unavoidable, relation between consensus, probability and uncertainty, connecting their reasons to the intertwine of logos and ergon and tracing the limits of deliberative logocentrism